2018
DOI: 10.1590/s0102-865020180060000001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant extract counteracts the effects of aging on cortical spreading depression and oxidative stress in the brain cortex

Abstract: Murici extract supplementation seems to revert detrimental effects in aged brains and could be considered as a strategy in the treatment of pathologies related to aging and cortical spreading depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…GSH/GSSG is considered a key indicator of oxidative stress [56,57]. In particular, the increase in the ratio indicates a decrease in cellular oxidative stress [58][59][60]. As shown in Figure 5, we found that in LPS-treated THP1 M0 cells the pre-treatment for 2 h with Cfr-LEO induced the increase of the GSH/GSSG ratio compared to no pre-treated cells, indicating the ability of Cfr-LEO to counteract the LPS-induced oxidative stress.…”
Section: Protective Effects Of Cfr-leo On Lps-activated Macrophagesmentioning
confidence: 99%
“…GSH/GSSG is considered a key indicator of oxidative stress [56,57]. In particular, the increase in the ratio indicates a decrease in cellular oxidative stress [58][59][60]. As shown in Figure 5, we found that in LPS-treated THP1 M0 cells the pre-treatment for 2 h with Cfr-LEO induced the increase of the GSH/GSSG ratio compared to no pre-treated cells, indicating the ability of Cfr-LEO to counteract the LPS-induced oxidative stress.…”
Section: Protective Effects Of Cfr-leo On Lps-activated Macrophagesmentioning
confidence: 99%
“…In this review, we revisit the theme of the influence of aging on electrophysiological aspects of brain signaling as indexed by the excitability-related phenomenon known as cortical spreading depression (CSD; Guedes et al, 1996; Farkas et al, 2011; Sousa et al, 2018). In addition, we examine how aging interacts with other factors, such as alcohol consumption (Abadie-Guedes et al, 2016), physical exercise, and nutritional status (Batista-de-Oliveira et al, 2012; Silva-Gondim et al, 2017), regarding the brain’s capability of generating and propagating CSD, which has been continuously investigated in our laboratory for many years (see Guedes, 2005, 2011; Abadie-Guedes et al, 2016, for an overview).…”
Section: Introduction: Aging and Brain Functionmentioning
confidence: 99%
“…Mitochondria isolated from aged rat cortex and hippocampus showed increased ROS production compared to young rats, which was not observed in mitochondria isolated from the cerebellum (8). Aging also decreased glutathione/oxidized glutathione ratio and increased lipid peroxidation levels and superoxide dismutase activity in cerebral cortex of 24-month-old Wistar rats compared to 3-month-old rats (9). Also, aging increased lipid peroxides and lipid hydroperoxides but decreased SOD activity in the cerebrum, cerebellum, and brainstem of 6-, 13-, 19-, and 26-month-old male albino rats compared to 3-month-old rats (10).…”
Section: Introductionmentioning
confidence: 74%